2018
DOI: 10.3389/fphar.2018.00431
|View full text |Cite
|
Sign up to set email alerts
|

GPCRomics: GPCR Expression in Cancer Cells and Tumors Identifies New, Potential Biomarkers and Therapeutic Targets

Abstract: G protein-coupled receptors (GPCRs), the largest family of targets for approved drugs, are rarely targeted for cancer treatment, except for certain endocrine and hormone-responsive tumors. Limited knowledge regarding GPCR expression in cancer cells likely has contributed to this lack of use of GPCR-targeted drugs as cancer therapeutics. We thus undertook GPCRomic studies to define the expression of endoGPCRs (which respond to endogenous molecules such as hormones, neurotransmitters and metabolites) in multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 61 publications
3
83
0
Order By: Relevance
“…For example, GPR68/OGR1 is strongly associated with CAFs in our analysis, 29 consistent with evidence that it is a novel functional receptor in PDAC-derived CAFs [13]. Similarly, epithelial-30 enriched GPCRs ( Figure 6E) are expressed in cancer cells [21] and as shown below, in cancer cell lines.…”
supporting
confidence: 84%
“…For example, GPR68/OGR1 is strongly associated with CAFs in our analysis, 29 consistent with evidence that it is a novel functional receptor in PDAC-derived CAFs [13]. Similarly, epithelial-30 enriched GPCRs ( Figure 6E) are expressed in cancer cells [21] and as shown below, in cancer cell lines.…”
supporting
confidence: 84%
“…As with an e-commerce site, this allows for serendipitous browsing, whereby the user may be able to discover lesser-known targets of significance to a topic of interest. This example will focus on GPCRs in cancer, as these proteins are rarely targeted in cancer treatments (Insel et al, 2018;Wu et al, 2019).…”
Section: Basic Protocol 2 Filter a Target List To Get Refined Resultsmentioning
confidence: 99%
“…A recent transcriptomics analysis demonstrated that most tumor types differentially express greater than 50 GPCRs, including many targets for approved drugs, but also a number of GPCRs largely unrecognized as targets of interest in cancer [47] and thereby adding to the growing list of these targeting opportunities. Such GPCRomics approaches [48] have highlighted potential therapeutic targets, such as GPR68 [47,49]. Research tools will be invaluable to further validate these potential targets for therapeutic relevance [50].…”
Section: Targeting Opportunities In the Therapeutic Gpcr-antibody Lanmentioning
confidence: 99%